Analisis Pengaruh Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan, Pajak Hotel Dan Pajak Restoran Terhadap Pendapatan Asli Daerah Kabupaten Alor - Sau Sabu, Junius Menase; Tang, Sefnat Aristarkus (Peneliti.net, 2023)
The purpose of this study was to determine the effect of Rural and Urban Land and Building Tax, Hotel Tax and Restaurant Tax on Local Revenue of Alor Regency. The analysis technique is descriptive analysis. The population in this study is all realization of Alor Regency Local Own Revenue, Urban and Rural Land and Building Tax, Hotel Tax and Restaurant Tax for the year of observation 2016-2020. The sampling method is purposive sampling. The statistical method in this study is multiple linear regression with the significance of the t test and F test as benchmarks for testing hypotheses and managing data using the help of the IBM SPSS 22 for windows program. This type of research is quantitative research with data collection techniques, observation, interviews and documentation. The results of the study prove that 1) Urban and Rural Land and Building Tax has a partial effect on Local Revenue of Alor Regency, thus H1 is accepted. 2) Hotel Tax has a partial effect on Local Revenue of Alor Regency, thus H2 is accepted. 3) Restaurant Tax has a partial effect on Local Revenue of Alor Regency, thus H3 is accepted. 4) Rural and Urban Land and Building Tax, Hotel Tax and Restaurant Tax simultaneously affect Alor Regency Local Revenue, so H4 is also accepted.